12-2k=k-7+7

Simple and best practice solution for 12-2k=k-7+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12-2k=k-7+7 equation:


Simplifying
12 + -2k = k + -7 + 7

Reorder the terms:
12 + -2k = -7 + 7 + k

Combine like terms: -7 + 7 = 0
12 + -2k = 0 + k
12 + -2k = k

Solving
12 + -2k = k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-1k' to each side of the equation.
12 + -2k + -1k = k + -1k

Combine like terms: -2k + -1k = -3k
12 + -3k = k + -1k

Combine like terms: k + -1k = 0
12 + -3k = 0

Add '-12' to each side of the equation.
12 + -12 + -3k = 0 + -12

Combine like terms: 12 + -12 = 0
0 + -3k = 0 + -12
-3k = 0 + -12

Combine like terms: 0 + -12 = -12
-3k = -12

Divide each side by '-3'.
k = 4

Simplifying
k = 4

See similar equations:

| 20w+-15w+-17=18 | | 2z+11=65-4x | | y=0.001x^2+0.3x | | 6(f+5)=2f+8 | | xy+3= | | k/72=0.8 | | 8(1-5n)+8n=200 | | 13.1=h+6.2 | | -6+25=m-10 | | -12=p-2 | | -2(5k-3)=86 | | 170m=1.54 | | -55x-20=0 | | 6+2p=10 | | 2c^2+5c+2=0 | | 3x-12+6=0 | | 170=1.54 | | 8a+3a=132 | | 18-b=13 | | 1-2/3y=12/5-1y/5 | | 7c+2c-8c=17 | | 8(1+5x)=-312 | | 3(3+5x)=2/3+3/7x | | -12a+3a=9 | | a+5=0.2(15+5a) | | -8(1+6v)=-104 | | x-1025=-2 | | 1.2(x-8)=1.9(x-1) | | x+66=14 | | 15m-6m-2m=14 | | -20x+5y=60 | | 6x-7=x-8 |

Equations solver categories